Vibro-acoustic optimisation of sandwich panels using the wave/finite element method. (15th November 2016) - Droz, C.; Zergoune, Z.; Boukadia, R.; Bareille, O.; Ichchou, M.N.
Abstract: This paper investigates the use of a wave-based method in the framework of structural optimisation of composite panels involving advanced components. The wave/finite element method (WFEM) is used to evaluate the influence of a core's geometry on the transition frequency of a sandwich panel involving composite skins. This transition occurs is a sandwich panel when the transverse shear stiffness has a significant influence on the flexural motion, compared to the bending stiffness. It follows that the modal density and the acoustic radiation will considerably increase above this frequency. The periodic waveguide is modelled at the mesoscopic scale using a 3D finite element model of the unit-cell. Therefore this method does not require an homogenisation of the core based on Gibson and Ashby formulations to provide the wave dispersion characteristics. Although the cellular cores compared in this study share the same mass-to-stiffness ratio, a significant alteration of the transition frequency and modal density can be observed compared to honeycomb cores. A periodic octagonal core is designed, providing up to 70% increase of the transition frequency and a significant reduction of the modal density.